Lgr4 is crucial for skin carcinogenesis by regulating MEK/ERK and Wnt/β-catenin signaling pathways. Issue 2 (28th December 2016) - Xu, Peng; Dang, Yongyan; Wang, Luyang; Liu, Xia; Ren, Xiaolin; Gu, Jun; Liu, Mingyao; Dai, Xing; Ye, Xiyun
Abstract: Lgr4 is a member of the leucine-rich, G protein–coupled receptor family of proteins, and has recently been shown to augment Wnt/β-catenin signaling via binding to Wnt agonists R-spondins. It plays an important role in skin development, but its involvement in skin tumorigenesis is unclear. Here, we report that mice deficient for Lgr4 are resistant to 12-O-tetradecanoyl-phorbol-13-acetate (TPA)-induced keratinocyte proliferation and papilloma formation. We show that TPA treatment activates MEK1, ERK1/2 and downstream effector AP-1 in wild-type (WT) epidermal cells and mice, but not in cells or mice where Lgr4 is depleted. Wnt/β-catenin signaling is also dramatically activated by TPA treatment, and this activation is abolished when Lgr4 is deleted. We provide evidences that blocking both MEK1/ERK1/2 and Wnt/β-catenin pathways prevents TPA-induced increase in the expression of Ccnd1 (cyclin D1), a known Wnt/β-catenin target gene, and that the activation of MEK1/ERK1/2 pathway lies upstream of Wnt/β-catenin signal pathway. Collectively, our findings identify Lgr4 as a critical positive factor for skin tumorigenesis by mediating the activation of MEK1/ERK1/2 and Wnt/β-catenin pathways. Highlights: Mice deficient for Lgr4 are resistant to TPA-induced keratinocyte proliferation and onset of papillomas. TPA treatment activated MEK1/ERK1/2/AP-1 and Wnt/β-catenin signaling pathways in vitro and in vivo in wild-type but not Lgr4 −/− mice. We provide evidence that MEK1/ERK1/2 pathway activation lies upstream of Wnt/β-catenin pathway activation during mouse skin tumor formation.